PENGUATAN PERAN APARATUR PEMERINTAHAN DESA DALAM MELAKSANAKAN TUGAS PEMERINTAHAN DESA DI KABUPATEN INDRAMAYU JAWA BARAT - Rasji Rasji (Jurnal Bakti Masyarakat Indonesia, 2021)
Village government is the lowest level of government in the Government of the Republic of Indonesia. Its existence is very strategic for the implementation of programs of the central government, local government, and the wishes of the village community, so that the village government can help create a balance between the goals desired by the state and those desired by the people, namely the welfare of the people. For this reason, the role of village government officials is important to achieve the success of implementing village government tasks. In fact, there are still many village government officials who have not been able to carry out their duties and authorities properly and correctly. How are efforts to strengthen the role of village government officials so that they are able to carry out their duties and authority properly and correctly? One effort that can be done is to provide technical guidance to village government officials regarding village governance, the duties and authorities of village government officials, as well as the preparation of village regulations. Through this activity, it is hoped that the role of the village government apparatus in carrying out their duties and authorities will be strong, so that their duties and authorities can be carried out properly and correctlyABSTRAK;Pemerintahan desa adalah tingkat pemerintahan terendah di dalam Pemerintahan Negara Republik Indonesia. Keberadaannya sangat strategis bagi penerapan program pemerintah pusat, pemerintah daerah, dan keinginan masyarakat desa, sehingga pemerintah desa dapat membantu terciptanya keseimbangan tujuan yang diinginkan oleh negara dan yang diinginkan oleh rakyat yaitu kesejahteraan rakyat. Untuk itu peran aparatur pemerintahan desa menjadi penting untuk mencapai keberhasilan pelaksanaan tugas pemerintahan desa. Pada kenyataannya masih banyak aparatur pemerintahan desa yang belum dapat melaksanakan tugas dan wewenangnya dengan baik dan benar. Bagaimana upaya menguatkan peran aparatur pemerintahan desa, agar mampu menjalankan tugas dan wewenangnya secara baik dan benar? Salah satu upaya yang dapat dilakukan adalah memberikan bimbingan teknis kepada aparatur pemerintahan desa mengenai pemerintahan desa, tugas dan wewenang aparatur pemerintah desa, maupun penyusunan peraturan desa. Melalui kegiatan ini diharapkan peran aparatur pemerintahan desa dalam melaksanakan tugas dan wewenangnya menjadi kuat, sehingga tugas dan wewenangnya dapat dilaksanakan dengan baik dan benar.